Ethics institutionalization in healthcare facilities in the Republic of Moldova - GRAMMA , Rodica (One Health & Risk Management, 2024)
Introduction. The process of institutionalizing ethics is composed of the implementation of tools such as: codes, ethical leadership, training, ethics committees, ethics audits, ethics consultants. The article presents an analysis of the situation on the role of these ethics’ tools on the activity of the healthcare facilities of the Republic of Moldova. Material and methods. The research was carried out on 2 target groups: 1. a cross-sectional study on a sample of 1070 employees of 120 hospital and primary care institutions and 2. a sample of 134 members of ethics / bioethics committees. Two questionnaires were developed and transposed into Google forms to be completed anonymously. Comparative evaluation was performed using the 95%CI. The standard Chi-Squared Test (α = 0.05) for Independence without Yates’ Correction was considered for 3x3 and 7x5 contingency tables. Results. In the country’s medical institutions, the level of institutionalization of ethics was low, and the application of ethics management tools varied significantly. Only 13% (95% CI: 11.0, 15.0) of respondents reported the existence of an institutional ethics code, while 30.4% (95% CI: 27.6, 33.1) admitted they were unaware of such a code within their institution. Furthermore, only 25.5% (95% CI: 22.9, 28.1) of respondents indicated that institutional values were promoted by all employees. Just 36.2% (95% CI: 30.4, 36.1) felt they had the necessary knowledge to make decisions in ethical dilemmas. Conclusions. The detected gaps lead us to the conclusion that the continuous integration of ethics into institutional activities must become essential for the managers of medical institutions in the country. This is an important condition for ensuring the quality of services. Implementing ethics programs should be an indispensable part of developing institutional strategies.